Status of Plant Invasion In India As Divulged From Kalidasa's Sanskrit Scriptures - Patil, Dinkarrao Amrutrao (Plantae Scientia, 2024)
Biodiversity is the mainstay of mankind and crucial for ecosystem functions. Although so, it is not stable and changing pattern of biodiversity are discernible worldwide on account of biological or plant invasion. Plant species are invaded intentionally, naturally or accidentally. Before embarking upon any developmental activities in a region, we have to take a stock of scenario about the status of biodiversity. In this regard, the present author made a headway collecting evidences of plant invasion (bioinvasion) on Indian subcontinent. Kalidasa's ancient Sanskrit scripts viz., Abhigyanshakuntalam, Meghaduta, Raghuvansham and Kumarsambhavam have been assessed from the viewpoint of plant invasion in India, the results of this study are being presented in this communication. This account may aid in the history of bioinvasion in India in view of biodiversity management.